Stenofilol B dan Hopeafenol, Dua Oligomer Stilbenoid dari Kayu Batang - Sri Atun; Sjamsul Arifin Achmad; Euis Holisotan Hakim; Yana Maolana Syah; Emilio L Ghisalberti; Lia Dewi Juliawaty (Jurnal Matematika & Sains, 2003)
Two oligostilbenoid, namely stenophyllol B (1) and hopeaphenol (2) had been isolated from the stem bark of Vatica umbonata Burck (Dipterocarpaceae). The structure of both compounds were elucidated based on spectroscopic data. Both compounds exhibited strong toxicity againts murine leucaemia cell P-388 with IC50 : 8,5 Î¼g/ml and 2,9 Î¼g/ml, respectively.